COVID-19 food price monitor - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
The Food Security Portal's COVID-19 Food Price Monitor serves as a temperature check of market conditions for staple and non-staple foods at the local level. Food prices strongly influence livelihoods and dietary choices made by farmers, traders, processors, and consumers. When markets are tight, prices are sensitive to shocks such as a bad harvest or, in today’s context, supply disruptions caused by COVID-19. For the poor who spend most of their income on food, any food price increase may put their food security at risk. Price spikes could point at supply disruptions and, this way, the Monitor helps identify hotspots in food chains. The Food Price Monitor provides daily updates of prices in wholesale and retail markets for a wide range of food products. Alerts refer to price changes from the start of social distancing measures taken because of COVID-19.